(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2010)
Fast Dissolving Tablet (FDT) of Raloxifene was prepared by direct-compression method by incorporating super disintegrants like crosscarmellose sodium and sodium starch glycolate. The study was performed by incorporating the super disintegrants in 2 % and 4 % concentration for each and 2 % - 2 % in combination of both super disintegrants. Five formulations having super disintegrants at different concentration levels were prepared to assess their efficiency. Different types of evaluation parameters for tablets were performed. Tablets containing super disintegrants in combination showed excellent in vitro dispersion time and drug release as compared to other formulations.